Influence of distributive justice on organizational citizenship behaviors: The mediating role of gratitude - Bala Subramanian, R.; Srikanth, P. B.; Thakur, Munish (Frontiers in Psychology, 2022)
Distributive justice is known to have important emotional and affective outcomes. The present study explores the role of distributive justice as an antecedent to feelings of gratitude towards the organization. Borrowing from social exchange theory we investigate the mediating role of gratitude in the relationship between perceived fairness in distributive justice and employees' organization citizenship behaviors. Multi-source data was collected from 185 employees and their supervisors employed in a large manufacturing organization based in East India. Data collection spanned two-time intervals. Data were analyzed using structured equation modeling. The results indicate that feelings of gratitude not only signal fair distribution of benefits such that the employees go beyond the call of the duty to invest in OCB by engaging in such acts, they presumably repay their social debts highlighted in the social exchange perspective. Implications for theory and practice are discussed.